The effects of ethnic and social segregation on children and adolescents: Recent research and results from a German multilevel study. - Oberwittler, Dietrich (My University, 2007)
Das Arbeitspapier berichtet über die aktuelle Forschungsliteratur zu den Auswirkungen ethnischer und sozialer Segregation auf Kinder und Jugendliche sowie über die Ergebnisse einer empirischen Studie zu diesem Thema, die der Autor in 61 Stadtvierteln durchgeführt hat. In der gegenwärtigen Forschung werden die Auswirkungen von Segregation als mögliche Kontexteffekte des Stadtviertels jenseits der individuellen Effekte sozialer Benachteiligung anhand geschachtelter Stichproben von Individuen in unterschiedlichen Stadtvierteln und mit Hilfe der Mehrebenenanalyse untersucht. Die theoretischen und methodischen Grundlagen dieses Ansatzes werden diskutiert. In den Ergebnissen gibt es einzelne empirische Hinweise auf die Existenz nachteiliger Effekte der Segregation in den Bereichen Gesundheit, Bildung und Kriminalität, doch stammen diese überwiegend aus U.S.-amerikanischen Studien, während europäischen Studien in diesem Bereich seltener sind und weniger eindeutige Ergebnisse hervorgebracht haben.

The paper, in a first part, reviews current literature on the effects of ethnic and social segregation on children and adolescents. In a second part, it reports results of an empirical study on this issue conducted by the author in two German cities. In recent research, the effects of segregation have been framed as possible 'contextual effects' of neighbourhoods, i.e. as separate factors beyond the individual effects of social disadvantage. The paper discusses theoretical and methodological underpinnings of recent studies that use nested samples of individuals in different types of neighbourhoods and multilevel analyses. While there is some evidence of detrimental effects of segregation on outcomes like health, education and crime, this mostly comes from the US. In Europe few relevant studies have been conducted and support for these hypotheses is much weaker. Results from a German multilevel study based on a sample of more than 5000 adolescent respondents in 61 neighbourhoods stress the importance of peergroups and 'agency' in shaping the influence of neighbourhoods on individual attitudes and behaviour. Social segregation in general seems to be more salient than ethnic segregation, and schools turn out to be important as developmental contexts independent from the residential neighbourhoods. Contrary to theoretical expectations, neighbourhood effects seem to be mainly restricted to native German adolescents, and girls show different patterns of effects than boys. Given the patchy evidence, more research on the overlapping contexts of schools and neighbourhoods in a develop-mental perspective is required.
Keywords: Kind; Integration; Segregation; Stadtquartier; Stadtteil; Armut; Bildung; Ausländer; Kriminalität; Empirische Sozialwissenschaft; Problemraum; Sozialverhalten; Stadtsoziologie; Sprache; Benachteiligung; Benachteiligter Stadtteil